Integrated utilization of microalgae cultured in aquaculture wastewater : wastewater treatment and production of valuable fatty acids and tocopherols - Tossavainen, Marika; Lahti, Katariina; Edelmann, Minnamari; Eskola, Reetta; Lampi, Anna-Maija; Piironen, Vieno; Korvonen, Pasi; Ojala, Anne; Romantschuk, Martin (Journal of Applied Phycology, 2019)
Microalgal cultivation in aquaculture wastewater (AWW) from recirculating aquaculture systems (RAS) is an approach for combined production of valuable algal biomass and AWW treatment. The growth, nutrient uptake, fatty acid (FA) profile, and tocopherol content of mixed algal cultures of Euglena gracilis with Selenastrum grown in AWWs from pikeperch (Sander lucioperca) and catfish (Clarias anguillaris) RAS were studied. The highest algal biomass (1.5gL(-1)), lipid (84.9mgL(-1)), and tocopherol (877.2gL(-1)) yields were achieved in sludge-amended pike perch AWW. Nutrient removal rates in experiments were 98.9-99.5 and 98.4-99.8% for NH4-N and PO4-P, and 75.4-89.2% and 84.3-95.7% for TN and TP, respectively, whereas the COD was reduced by 45.8-67.6%. Biomass EPA and DHA content met, while ARA and tocopherol content exceeded the requirements for fish feed. Algal cultivation in AWWs is a promising alternative for AWW treatment while providing a replacement for fish oil in feed. Peer reviewed